Phase field modelling of dendritic solidification under additive manufacturing conditions - Tang, Chao (2022)
Melting and solidification in metal-based additive manufacturing (AM) ultimately determine the crystallographic texture, cellular/columnar dendritic growth, solute segregation, and resultant materials properties. The microstructure of AM-built alloys is closely related to various physics during the printing process. In the present study, a multi-physics model was developed to simulate the evolution of grain and dendritic-scale microstructure during laser AM of a Ni-based alloy. Computational fluid dynamics was used to simulate the melt pool dynamics and temperature distribution for the laser powder bed fusion process. Using Ni-Nb as an analogue to Inconel 625, a phase field model was applied to predict the microstructural features within a two-dimensional solidified melt pool. The predicted results exhibit fair agreement with experimental characteristics in the literature, including melt pool profile, dendrite size, dendrite morphology, and crystallographic texture. The multi-physics model paves the way for computationally predicting the chemistry-process-structure relationship in AM-built alloys, which helps to understand the fundamental physics of AM solidification.